What do the amendments to the law on the High Judicial and Prosecutorial Council of Bosnia and Herzegovina bring? - Milinković Igor (Glasnik Advokatske komore Vojvodine)
Judicial independence represents one of the key prerequisites for the rule of law. However, fostering a "culture" of judicial independence must be accompanied by continuous efforts to improve mechanisms and the "culture" of accountability and integrity of judicial office holders. This necessity is particularly emphasized in post-authoritarian societies, where judicial independence rests on the unstable foundations of an authoritarian past characterized by systematic undermining of judicial autonomy. In recent decades, the establishment of judicial councils has been recognized as a tool for strengthening judicial independence. Judicial councils, independent bodies predominantly composed of representatives of the judiciary, "are designed to remove the functions of appointment, promotion decisions, and disciplinary actions against judges from partisan political processes while simultaneously ensuring a certain level of accountability" (Garoupa, Ginsberg, 2009). In recent years, however, warnings have increasingly emerged that the formation of judicial councils can open new channels for the politicization of the judiciary, bringing the issue of accountability of council members into focus. This paper analyzes the provisions of the Law on Amendments to the Law on the High Judicial and Prosecutorial Council of Bosnia and Herzegovina (HJPC BiH), adopted in 2023, concerning the disciplinary liability of judges and council members, as well as the procedures for the removal of HJPC BiH members. The paper will also highlight other provisions of this law aimed at combating corruption in the judiciary and strengthening the integrity of judicial office holders.